2015
DOI: 10.1038/bmt.2014.331
|View full text |Cite
|
Sign up to set email alerts
|

Donor HLA-specific Abs: to BMT or not to BMT?

Abstract: The engraftment failure associated with Abs to donor-specific HLA (DSA) limits options for sensitized BMT candidates. Fourteen of fifteen patients with no other viable donor options were desensitized and transplanted using a regimen of plasmapheresis and low-dose i.v. Ig modified to accommodate pre-BMT conditioning. DSA levels were assessed by solid-phase immunoassays and cell-based crossmatch tests. DSA levels were monitored throughout desensitization and on day − 1 to determine if there was any DSA rebound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 37 publications
2
43
0
1
Order By: Relevance
“…Este procedimiento terapéutico inicia una a 2 semanas antes del condicionamiento, dependiendo del título previo de anticuerpos y de la respuesta al tratamiento. (GRADE B1) 283 R Si bien se ha utilizado suplencia de IgIV en niños con hipogammaglobulinemia secundaria a quimioterapia altamente inmunosupresora, así como en protocolos de investigación que incluyen rituximab para enfermedades neoplásicas, no hay evidencia disponible que respalde estas indicaciones. (GRADE D)…”
Section: Enfermedad Renal Crónicaunclassified
“…Este procedimiento terapéutico inicia una a 2 semanas antes del condicionamiento, dependiendo del título previo de anticuerpos y de la respuesta al tratamiento. (GRADE B1) 283 R Si bien se ha utilizado suplencia de IgIV en niños con hipogammaglobulinemia secundaria a quimioterapia altamente inmunosupresora, así como en protocolos de investigación que incluyen rituximab para enfermedades neoplásicas, no hay evidencia disponible que respalde estas indicaciones. (GRADE D)…”
Section: Enfermedad Renal Crónicaunclassified
“…In patients without alternative available donors, Gladstone et al found that plasmapheresis combined with anti-cytomegalovirus (CMV) intravenous immunoglobulin, tacrolimus, and mycophenolate mofetil (MMF) starting 1-2 weeks prior to conditioning, depending on the level of DSA, was associated a 64.4% mean reduction in DSA levels [17,20]. Fifteen patients received this treatment and the 14 patients who achieved DSA reduction to negative or weak levels underwent transplantation and engrafted.…”
Section: Donor-specific Antibodiesmentioning
confidence: 99%
“…138,139 In patients with detectable DSAs to all potential HLA-haploidentical donors, desensitization procedures can reduce DSA titres such that haploBMT can be successfully performed. 138,140 Notably, Epstein-Barr virus-related post-transplantation lymphoproliferative disease within the first year post-transplantation was not seen among 785 patients treated with PTCy, 141 and no increase in donor-derived malignancies was detected. 142 …”
Section: Clinical Outcomesmentioning
confidence: 99%